Risk Management Evaluation in Murabahah Financing at BNI Syariah Bank Makassar Branch - Firdawati (JEKAMI Journal of Accounting, 2022)
The results in this study are the Bank BNI Syariah Makassar Branch conducts risk management evaluation to anticipate and minimize the risks that arise in murabahah financing. The risks that often arise are credit risk and operational risk. Bank BNI Syariah Makassar Branch implements risk management with a process of identification, measurement, monitoring and risk control. Risk identification process using the 5C principles, risk measurement using stress testing and determining customer scoring, monitoring risk through risk profiles and monitoring customers and her business, finally controlling risk through internal control & restructuring stage, namely rescheduling & reconditioning. Bank BNI Syariah Makassar Branch also handle emerging risks and creates new strategies during the covid-19 pandemic. Bank BNI Syariah Makassar Branch continues to evaluate and develop policies that are set to improve the implementation of risk management, especially in the financing of murabahah.